Unclear Public Policy: The Real Barrier in Recognizing Foreign Arbitration Awards? - Sugianto, Fajar; Athina Indradewi, Astrid; Antonius Sanjaya, Robin; Yamamoto, Atsuko (Indonesian State Law Review, 2025)
In Indonesia, a foreign arbitral award refers to a decision issued by an arbitration institution or arbitrator outside the country or recognized as such under Indonesian law. This classification reflects Indonesia’s adherence to the principle of territoriality in distinguishing arbitration awards as "international." However, enforcement remains contentious due to courts' broad interpretation of public policy under Article 66(c) of Law No. 30 of 1999. Despite Constitutional Court Decision No. 100/PUU-XXII/2024, the lack of a clear definition of public policy persists, leaving courts to determine its scope on a case-by-case basis. Until further regulations provide clarity, Article 66(c) will remain ambiguous and continue to be a basis for challenging foreign awards. A comparison with Singapore highlights two key findings. First, Indonesia applies a broad and inconsistent interpretation of public policy, while Singapore’s approach is narrower and more predictable. Second, Indonesian courts lack uniformity, as shown in three patterns: (1) awards are rejected for allegedly breaching sovereignty by restricting access to local courts; (2) awards are annulled for contravening Indonesian laws; and (3) awards are refused for endangering national interests. Rather than redefining international arbitration awards, Indonesia needs clearer guidelines and consistent application of public policy to enhance investor confidence and its global arbitration competitiveness.